PENGARUH STRATEGI INSIDE OUTSIDE CIRCLE TERHADAP HASIL BELAJAR SISWA PADA TEMA INDAHNYA KERAGAMAN DI NEGERIKU KELAS IV SD SUBSIDI SWAKARYA T.A. 2020/2021 (JS (JURNAL SEKOLAH), 2021)
Abstract: The Influence of Inside Outside Circle Strategy On Student Learning on The Beautiful of My Country™s Diversity Theme at 4 Primary Class at Subsidi Swakarya T.A 2020/2021. The purpose of this study was to determine the effect of the Inside Outside Circle strategy on student learning outcomes on the theme The Beauty of Diversity in my Country, grade IV SD Subsidi Swakarya T.A. 2020/2021. The population of this study was all 121 students of grade VI SD Subsidi Swakarya. Samples were taken randomly as many as 40 people, 20 people for the experimental class and 20 people for the control class. This type of research is experimental research. The instrument used in this research is a multiple choice test. The average value of the experimental class is 77.25. As for the control class is 66.25. Thus, it can be said that the average value of student learning outcomes in the experimental class is higher than the control class. The data were analyzed by hypothesis testing using the "t" test followed by a significant test at the real level = 0.05. Based on these results, there are differences between the Inside Outside Circle strategy and conventional learning strategies. From the results of hypothesis testing, it was obtained that tcount > ttable was 7,442 > 1,707 at level = 0,05. Thus Ho is rejected and Ha is accepted, so it can be stated "There is a significant influence on the Inside Outside Circle strategy on student learning outcomes on the theme The Beauty of Diversity in My Country Class IV Subsidized Elementary School T.A. 2020/2021 has been verified. Based on the explanation described above, it can be concluded that the Inside Outside Circle strategy can affect student learning outcomes.Keywords: Learning Outcomes, Learning Strategies, Inside Outside CircleAbstrak : Pengaruh Strategi Inside Outside Circle Terhadap Hasil Belajar Siswa Pada Tema Indahnya Keberagaman Di Negeriku Kelas 4 SD Subsidi Swakarya T.A 2020/2021.Tujuan penelitian ini adalah untuk mengetahui pengaruh strategi Inside Outside Circle terhadap hasil belajar siswa pada tema Indahnya Keragaman di Negeriku kelas IV SD Subsidi Swakarya T.A. 2020/2021. Populasi penelitian ini adalah seluruh siswa kelas VI SD Subsidi Swakarya sebanyak 121 orang. Sampel diambil random kelas sebanyak 40 orang, 20 orang untuk kelas eksperimen dan 20 orang untuk kelas kontrol. Jenis penelitian ini adalah penelitian eksperimen. Instrumen yang digunakan dalam penelitian ini adalah tes yang berbentuk pilihan berganda. Nilai rata-rata kelas eksperimen adalah 77,25. Sedangkan untuk kelas kontrol adalah 66,25. Dengan demikian, dapat dikatakan bahwa nilai rata-rata hasil belajar siswa kelas eksperimen lebih tinggi daripada kelas kontrol. Data dianalisis dengan uji hipotesis menggunakan uji œt yang dilanjutkan dengan uji signifikan pada taraf nyata Î± = 0,05. Berdasarkan hasil tersebut terdapat perbedaan antara strategi Inside Outside Circle dengan strategi pembelajaran konvensional. Dari hasil uji hipotesis diperoleh thitung > ttabel yaitu 7,442 > 1,707 pada taraf Î± = 0,05. Dengan demikian Ho ditolak dan Ha diterima sehingga dapat dinyatakan œAda pengaruh yang signifikan pada strategi Inside Outside Circle terhadap hasil belajar siswa pada tema Indahnya Keragaman di Negeriku Kelas IV SD Subsidi Swakarya T.A. 2020/2021 teruji kebenarannya. Berdasarkan penjelasan yang telah dipaparkan di atas maka dapat ditarik kesimpulan bahwa strategi Inside Outside Circle dapat berpengaruh terhadap hasil belajar siswa.Kata Kunci : Hasil Belajar, Strategi Pembelajaran, Inside Outside Circle